QT prolongation and cardiac toxicity of new tuberculosis drugs in Europe: a Tuberculosis Network European Trialsgroup (TBnet) study. Issue 2 (16th August 2018) - Guglielmetti, Lorenzo; Tiberi, Simon; Burman, Matthew; Kunst, Heinke; Wejse, Christian; Togonidze, Tamar; Bothamley, Graham; Lange, Christoph
There is concern that many second-line drugs used to treat multidrug-resistant tuberculosis (MDR-TB) may cause fatal arrhythmias linked to QT interval prolongation. The QT interval, measured on an electrocardiogram (ECG), represents the duration of the ventricular electrical systole. In order to have a more reproducible value across time and heart rates, the QT interval is adjusted according to heart rate (as QTc). Fluoroquinolones and, possibly, clofazimine can prolong the QTc interval [1, 2], as do bedaquiline (Bdq) and delamanid (Dlm) [3, 4]. A QTc interval >500 ms is considered a risk factor for ventricular arrhythmias such as torsades de pointes (TdP) [5]. Overall, 10–20% of patients with drug-induced TdP have a genetic predisposition and more than 70% have at least two other risk factors, like older age, female sex and electrolyte disturbances [6]. In smaller cohorts, no cases of fatal arrhythmia have been reported in association with new tuberculosis (TB) drugs and deaths in Bdq/Dlm registration trials were not linked to prolonged QTc nor arrhythmias [3, 4, 7]. The objective of the study was to evaluate the clinical impact of QTc prolongation and the number of cardiac events in patients receiving Bdq/Dlm treatment for MDR-TB in treatment centres of the Tuberculosis Network European Trialsgroup (TBnet), a clinical research collaboration of the European Respiratory Society, within the World Health Organization (WHO) Europe region. Few cardiac arrhythmias and no fatalities were observed in MDR-TB patients treated with bedaquiline and delamanid http://ow.ly/2tC030koXJa